2014
DOI: 10.4239/wjd.v5.i2.89
|View full text |Cite
|
Sign up to set email alerts
|

New insights into insulin: The anti-inflammatory effect and its clinical relevance

Abstract: Hyperglycemia, a commonly exhibited metabolic disorder in critically ill patients, activates the body's inflammatory defense mechanism, causing the waterfall release of numerous inflammatory mediators and cytokines, and eventually leads to organ damage. As the only glucose-lowering hormone in the body, insulin not only alleviates the detrimental effects of hyperglycemia through its metabolic regulation, but also directly modulates inflammatory mediators and acts upon immune cells to enhance immunocompetence. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
147
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(159 citation statements)
references
References 71 publications
6
147
1
5
Order By: Relevance
“…In our study, no significant difference was found between the non-DKA and the control groups regarding serum BChE activity ( p  > 0.05), while a previous study reported a significant difference between them [21]. The insignificant difference in our results may be due to the regular insulin therapy and good glycemic control of the non DKA group which inhibited inflammation and reduced oxidative stress [28, 29]. …”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…In our study, no significant difference was found between the non-DKA and the control groups regarding serum BChE activity ( p  > 0.05), while a previous study reported a significant difference between them [21]. The insignificant difference in our results may be due to the regular insulin therapy and good glycemic control of the non DKA group which inhibited inflammation and reduced oxidative stress [28, 29]. …”
Section: Discussioncontrasting
confidence: 69%
“…During DKA management, receiving insulin and fluid therapy abolishes the cascade of releasing inflammatory mediators and cytokines, which in turn inhibits platelet activation and increase serum BChE activity. Insulin therapy inhibits hyperglycemia, thus attenuates glucose-mediated inflammation, which suppresses pro-inflammatory cytokines and induces anti-inflammatory mediators [28]. Correction of dehydration and hypoperfusion by fluid therapy, reduces lactic acidosis which in turn decreases inflammatory mediators release [2].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that insulin may exert an anti-inflammatory response, independent of its effects on glycemia (76,77). Insulin has been shown to alleviate inflammation through several mechanisms, including increased endothelial nitric oxide release and decreased expression of proinflammatory cytokines and immune mediators, such as NF-kB, intracellular adhesion molecule-1, and MCP-1, as well as several TLRs (76).…”
Section: Insulinmentioning
confidence: 99%
“…Insulin has been shown to alleviate inflammation through several mechanisms, including increased endothelial nitric oxide release and decreased expression of proinflammatory cytokines and immune mediators, such as NF-kB, intracellular adhesion molecule-1, and MCP-1, as well as several TLRs (76). In a randomized parallel-group study in patients with type 2 diabetes, serum concentrations of hs-CRP and IL-6 were markedly reduced in insulin-treated patients compared with metformin, despite similar glycemic control (78).…”
Section: Insulinmentioning
confidence: 99%
“…Дизре-гуляция глюкозных транспортеров GLUT 4 и GLUT 8, преимущественно в гиппокампе и миндалине головного мозга, характерна для нейровоспаления. HMGB 1 белки предложены в качестве биомаркеров метаболического синдрома, сопровождающегося развитием инсулинорези-стентности [64]. Реализация TLR4-зависимого механиз-ма врожденного иммунитета способствует проявлению инсулинорезистентности.…”
Section: секреторный фенотип стареющих клетокunclassified